Ultrasound-Guided Biopsy of Pleural-Based Pulmonary Lesions by Injection of Contrast-Enhancing Drugs - Fu, Ying; Zhang, Yuan-Yuan; Cui, Li-Gang; Tan, Shi; Sun, Yan (Frontiers in Pharmacology, 2019)
In this study, a total of 58 patients with single subpleural pulmonary lesions (males: 36, females: 22, mean age: 63 ± 16.2 years) who underwent CEUS and had a definite diagnosis (benign lesions:25, malignant lesions:33) were enrolled. After the contrast agent injection, the arrival times, intensity and uniformity of enhancement, as well as the display rate of internal necrosis were recorded and compared between malignant and benign lesions. Furthermore, the nodules were divided into two size subgroups: ≥5 cm (group 1), and <5 cm (group 2). The display rate of internal necrosis and change of pre-scheduled puncture paths were compared between subgroups. Also, the number of biopsies, diagnostic accuracy rate, and the incidence of complications were recorded. Finally, internal necrosis was demonstrated in 20 of 58 lesions (34.5%). There was a statistically significant difference in the arrival times and intensity of enhancement between benign and malignant lesions (p < 0.05). Sixteen of them had changed the planned puncture path due to the large necrosis area (80%, 16/20). For lesions in group 1, necrosis was found in 15 lesions and there was a statistically significant difference in the necrosis rate between the two subgroups (15/26 vs 5/32, p = 0.001). The change in the pre-scheduled puncture path occurred in 12 patients in group 1 while 4 patients in group 2 exhibited a change in the planned puncture path (p = 0.004). The average number of punctures was 2.9 ± 0.7 times. The total diagnosis rate was 98.3%. Local pneumothorax occurred in 2 patients. Hemoptysis occurred in 1 patient. No serious complications occurred. In conclusion, CEUS guided biopsy is an effective, sensitive, and safe method for the diagnosis of pleural-based pulmonary lesions by facilitating a distinction between necrosis and active tissue. The current findings indicated that CEUS before a biopsy may be especially vital in lesions ≥ 5 cm.